HUBUNGAN PENGETAHUAN MAHASISWA TENTANG PELAKSANAAN UJIAN KOMPETENSI NASIONAL DENGAN MOTIVASI BELAJAR MAHASISWA TINGKAT III PROGRAM STUDI S1 KEPERAWATAN STIKES KURNIA JAYA PERSADA PALOPO - Grace Tedy Tulak; Rahmayanti Jus’an (Lembaga Penerbit dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
One of the efforts to encourage the acceleration of improvement and equality of health personnel education is by increasing the quality control of educational graduates. The national competence test is one effective way to improve the educational process and to sharpen the achievement of competency relation according to the competency standard.His study aims to analyze correlation of students' knowledge about the implementation of national competence test with student learning motivation Reguler Level III Study Program S1 Nursing STIKes Kurnia Jaya Persada Palopo 2017. Research conducted in August Type of research used is quantitative research with descriptive correlational design. The research design is cross sectional study. The sample size is 57 people. Sampling using total sampling. The research instrument is questionnaire and data processing using SPSS version. 2.2.The result of the research shows that 37 respondents (64,9%) have good knowledge about national competence test, 32 respondents (56,1%) have high learning motivation and 5 respondents (8,8%) have learning motivation low. While the students who have less good knowledge about the implementation of national competence test as many as 20 respondents (35.1%) of which there are 9 respondents (15.8%) who have high learning motivation and 11 respondents (19.3%) who have motivation low learning. The result of chi square test shows that p-value = 0.001 is smaller than α = 0,05 meaning that there is correlation between student's knowledge about the implementation of national competence test with student learning motivation at level III of nursing program STIKes Kurnia Jaya Persada Palopo year 2017.Thus, students are expected to improve knowledge of nursing science accompanied by high motivation and interest to be able to pass with quality quality. Keywords : Knowledge, Competency Test, Learning Motivation